Cross-laminated timber: a renewable structural system - Strahm, Joshua (Kansas State University, 2019)
Developed in Europe in the early 1990’s, cross-laminated timber (CLT) is beginning to make its way into the North American building construction market. Similar to other types of engineered wood products, such as Glulam, CLT is an efficient and economical way to use natural wood resources. This report introduces the product with its structural characteristics, advantages and disadvantages, manufacturing, and construction. ANSI/APA PRG 320 Standard for Performance-Rated Cross-Laminated Timber published by APA – The Engineered Wood Association is the manufacturing standard for CLT in the United States. Manufacturers will supply reference design values for design engineers to check the strength of CLT members. Methods used to determine reference design values include experimental and analytical studies. CLT has many benefits in construction but also has challenges due to architects’, engineers’, and contractors’ unfamiliarity with the product. A few projects have been built using CLT in the United States including a building at Oregon State University and one at the University of Arkansas.
Keywords: Cross laminated timber; Shear analogy